The Effect of Different Bone and Analytical Methods on the Assessment of Bone Mineralization to Dietary Phosphorus, Phytase, and Vitamin D in Finishing Pigs - Hadley R. Williams; Jordan T. Gebhardt; Mike D. Tokach; Jason C. Woodworth; Robert D. Goodband; Joel M. DeRouchey; Jon R. Bergstrom; Chad W. Hastad; Zach B. Post; Michael C. Rahe; Christopher L. Siepker; Panchan Sitthicharoenchai; et al. (Kansas Agricultural Experiment Station Research Reports, 2022)
Eight hundred eighty-two pigs (initially 73.2 ± 0.7 lb) were used to evaluate the effects of different bones and analytical methods on the assessment of bone mineralization response to dietary P and vitamin D in growing-finishing pigs. Pens of pigs (20 pigs per pen) were randomized to 1 of 5 dietary treatments in a completely randomized design with 9 pens per treatment. Treatments were formulated to have varying levels of P, phytase, and vitamin D to potentially provide wide differences in bone characteristics. After feeding diets for 112 d, nine pigs per treatment were euthanized for bone, blood, and urine analysis. There were no significant differences for final BW, ADG, ADFI, F/G (P>0.10), or bone ash (bone ash × bone interaction,P>0.10) regardless of the ashing method. The response to treatment for bone density and bone mineral content was dependent upon the bone (density interaction,P= 0.053; mineral interaction,P= 0.078). There were no treatment differences for bone density and bone mineral content for metacarpals, fibulas, and 2nd rib (P>0.05). For 10th rib bone density, pigs fed industry levels of P and vitamin D had increased (P<0.05) bone density compared to pigs fed NRC levels with phytase, with pigs fed deficient P, NRC levels of P with no phytase, and extra 25(OH)D3vitamin D (HyD) intermediate. Pigs fed extra vitamin D from HyD had increased (P<0.05) 10th rib bone mineral content compared to pigs fed deficient P and NRC levels of P with phytase, with pigs fed industry P and vitamin D, and NRC P with monocalcium intermediate. In summary, bone density and bone mineral content responses varied depending on the bone. The difference between bone ash procedures was more apparent than the differences between diets. Differences in bone density and mineral content in response to P and vitamin D were most apparent with the 10th ribs.
Keywords: bone mineralization; finishing pigs; growth performance